THIRTY YEARS OF FAMILY MEDICINE SPECIALTY IN POLAND: A CASE STUDY OF ITS INSTITUTIONALIZATION, PRACTICE, AND PATIENT PERCEPTION WITHIN PRIMARY HEALTHCARE: Thirty Years of Family Medicine Specialty in Poland - Guziak, Mateusz (Srpski medicinski časopis Lekarske komore, 2025)
Background: Family medicine (FM) specialty in Poland was introduced in the early 1990s as part of broader health reforms aimed at restructuring primary healthcare (PHC) and improving access, continuity, and coordination of care. Despite three decades of development, FM continues to face systemic and professional challenges within the Polish healthcare system. Objective: This study used a case study approach to explore the evolution of family medicine specialty in Poland, examining its institutional foundation, specialist training, its role in PHC delivery, and patient satisfaction with services. Methods: An explanatory case study design was employed, drawing on policy documents, training curricula, peer-reviewed literature, and national statistics. Thematic analysis was guided by a framework for case study evaluation in healthcare systems. Results: Family medicine specialty has gained full recognition as a clinical and academic specialty in Poland. However, only a minority of PHC physicians are formally trained in FM. While the postgraduate training program aligns with European standards, it lacks longitudinal assessment and consistent quality of supervision. Patients report generally high satisfaction with interpersonal aspects of care but rate family medicine lower than specialist services in areas such as communication, empathy, and emotional support. The specialty also faces recruitment difficulties, with many FM residency slots unfilled despite financial incentives. Conclusion: Family medicine specialty in Poland has achieved significant structural milestones but remains underutilized and undervalued within the broader PHC system. Reforms should prioritize strengthening its educational pathways, improving working conditions, and addressing public perceptions. Enhancing communication skills and increasing the visibility of family physicians could improve both patient satisfaction and the attractiveness of the specialty.